MODELOS DE EXALAÇÃO DE RADÔNIO EM PAISAGENS TROPICAIS ÚMIDAS SOBRE GRANITO - Rebelo 1, Antonio M. A.; Bittencourt, André V. L.; Mantovani, Luiz E. (Boletim Paranaense de Geociências, 2003)
Foram estabelecidas e analisadas as principais relações entre intensidades de exalação de radônio ( 222Rn e 220Rn) e os elementos morfológicos e dinâmicos de paisagens tropicais úmidas, com o objetivo de elaborar modelos de exalação de Rn adaptados a este tipo de paisagens, e aplicáveis na escala de pequenos núcleos habitacionais. Em uma vertente sobre rocha granítica com teores normais em U e Th, e caracterizada pela associação Latossolo-Solo Podzólico, os produtos de atuação dos processos supergênicos, com destaque para a transição de latolização em podzolização, e o atual regime hídrico do aqüífero freático, foram relacionados aos processos radioativos de geração, emanação e migração de Rn, verificando-se como tais inter-relações afetam a sua exalação nas paisagens. Tal abordagem foi fundamentada nos conceitos de sistema pedológico de transformação e de geoquímica de paisagens, além de conceitos da física e geologia nucleares e elementos climatológicos e hidrogeológicos do macroambiente, num enfoque interdisciplinar, tridimensional e sistêmico. Às vertentes configuradas em paisagens elementares; eluvial, transeluvial e supraqual associam-se diferentes geoformas, tipos e espessuras de solos residuais e radioanomalias com diferentes intensidades e formas de hospedagem de U e de Th. Com base em tais elementos, suas relações espaciais com o sistema freático, e considerando a umidade dos solos na capacidade de campo, as possibilidades de maiores taxas de exalação de Rn, sobretudo 222Rn, são nas paisagens supraqual e transeluvial. Na paisagem eluvial, a despeito da existência de intensas anomalias gama, devido principalmente ao acúmulo de minerais resistatos com U e Th e compostos de Th, os fluxos de Rn são menos significativos. Assim, no contexto enfocado, os produtos da alteração supergênica, organizados num sistema vertente, são materiais em que as taxas de exalação de radônio são mais elevadas do que as medidas na rocha inalterada subjacente. O entendimento do comportamento do U, Th, Ra e Rn no ambiente superficial tornou possível estabelecer modelos previsionais de exalação de Rn adaptados às paisagens elementares, em escalas compatíveis com pequenos núcleos habitacionais ou em unidades residenciais. RADON EXHALATION MODELS IN HUMID TROPICAL LANDSCAPES OVER GRANITE Extended Abstract The main relationships between radon ( 222 Rn and 220 Rn) exhalation intensities and the morpho-dynamic elements of humid tropical landscapes have been established and analyzed, aiming at elaborating Rn exhalation models adapted to this type of landscapes, to be used in the scale of small habitational nuclei. The present research revolved around the understanding of two distinct phases, each one presenting their own processes and time durations. The first one covers the modelling and internal constitution of a drainage basin slopes, during the geologic and pedologic times. The second one refers to the slope morphological system, structure of which is the result of previous processes, allowing for the current radioactive processes of Rn generation, emanation (figure 1), migration and exhalation, some of which affected by rain, temperature, pressure and winds. Such elements have proven to be relevant in the water regimen of the phreatic aquifer. Multi and interdisciplinary studies about the different areas approached were done, making use of several data, information and concepts from worldwide scientific literature. The focus of the study has been a slope over granite containing normal levels of U and Th, and characterized by the soil association Latosol-Podzolic (figure 2). The analyses were carried out in short spatial-temporal limits, according to the dimensions of the slopes, and, regarding time specifics, the pedologic scale was found to be the most relevant. Several aspects have been evaluated, namely the role of the supergenic processes on the evolution of the landscapes, the impact of this evolution on the efficiency of the radioactive processes mentioned, on the different soils and under different aquifer hydric regimens in these landscapes. In the studied soil, emphasis was placed on the concept of the transformation pedologic system and on the relative cronology of the main pedogenetic phases involved, namely latolization and podzolization. In the dispersion of radionuclides, fundamental concepts of surface geochemistry have been used, main emphasis on the ones of elementary landscape geochemistry (figure 2), and of element abundance, migration, flows, and geochemical barriers, backed up by the use of Th/U and Us/Ut (exchageable U/total U) ratios. Moreover, several concepts of nuclear physics, main focus on the 238 U and 232 Th decay series, and hydrogeologic and climatological elements of the environment have been addressed. In regard to the spatial-temporal dimensions stressed in this study, the chronology of the main pedogeochemical processes responsible for the re-distribution of U and Th, and the nature of their secondary hosting phases, it was assumed that the radionuclides of the series mentioned are in secular radioactive equilibrium. Such an approach allowed for the use of U and Th as indicators of the distribution of Ra, Rn precursor, which, in this study, is symbolized by the notation U and Th (Ra). In the models presented, the supergenic processes configurate the slopes in the eluvial, transeluvial, superaqual and aqual landscapes, this last one not considered in this study. Each of these landscapes is characterized by different geoforms, types and thickness of the residual soils and their permea-porosities, and associated to different radionuclides U and Th (Ra) concentrations and their respective hosting phases, as well as different water regimens of the phreatic aquifer (figure 2). The eluvial landscape is the place where Latosols mostly occur. In this case, the main U and Th (Ra) anomalies are located on the top of latosolic B horizon, and they are due to the relative accumulation of resistate minerals, insoluble Th compounds, and U and Th fixed to Fe and Al oxihydroxides and clays by adsorption. In this landscape, the aeration zone of the aquifer presents its maximum thickness, and the groundwater flows are vertical downward. In the transeluvial landscape, the dominant soils are the Podzolic, originated from the podzolization of the pre-existant Latosols. Moreover, the Latosol-Podzolic transformation system comprises a second generation of radioanomalies, more intense and with higher proportions of adsorbed U, and resultant from the reworking of the anomalies associated with the Latosols. Such a transforming phase is also responsible for the change in the existant versant slope angle and “permea-porosities”, forming a perched sub-system phreatic aquifer in this landscape (figure 2). The main concentrations of U and Th (Ra) are partly relative and partly absolute, and are located on the top of textural B horizon of the Podzoloic Soils, in hosting phases similar to the ones from the previous landscape, and containing organic matter as well. The groundwater flows are essentially lateral, the most superficial ones canalized through the A and E pedologic horizons of the perched sub-system aquifer. In the superaqual landscape, the radioanomalies are primarily uraniferous and absolute in nature, with U adsorbed to clays, organic matter and oxides of A0 and A1 horizons of the Hydromorphic Soils (figure 2), the migration of uraniferous solutions occurring in two principal phases. The first one, longer and older than 1 My, took place during latolization. The second phase, younger and affecting more limited geographic areas, occurred during the Latosols podzolization, between 100,000 and 500,000 years, having part of the solutions drained into the current drainage system. In this landscape, the groundwater flows are predominantly lateral during the rainy seasons, and vertical upward during dry seasons. Hence, the supergenic alteration products, organized on a slope system, are materials in which the rates of radon exhalation are higher than the ones measured on unaffected subjacent rock. Based on the secondary concentrations and hosting phases of U and Th (Ra), on the “permea-porosities” of the soils and their spatial relationships with the phreatic system, and considering the soil moisture content near the field capacity, the higher rates of Rn exhalation, mainly 222 Rn, are likely to happen in Hydromorphic Soils in the superaqual landscape and in Podzolic Soils in transeluvial landscape (table 1 and 2 and figure 2). This Rn exhalation rates are conditioned by a positive combination between Rn generation and emanation. Exceptions occur in areas under the influence of the current drainage system of the superaqual landscape, where 238 U younger than 1 My is in radioactive disequilibrium with their daughters, which causes a negative impact on Rn generation. In the eluvial landscape, despite the existance of high content of U and Th (Ra) associated with the Latosols, due to the accumulation of resistates with U and Th, Th compounds, and U and Th adsorbed in oxihydroxides and clays, the Rn fluxes are less important, and are controlled by the low emanation of most of the hosting phases mentioned (table 1). It is important to note that other soil moisture contents may affect the intensities of Rn fluxes significantly (table 2). At last the approach which has been used has led to an evaluation of Rn exhalation conditioning factors while referring to humid tropical landscapes. All kinds of parameters, climatic, geochemical, weathering, pedogenetic, morphogenetic and hydrogeologic parameters could be integrated into the scale of elementary landscape slope, and they all can be integrated among themselves and also to the radioactive processes of Rn generation, emanation, migration and exhalation, by means of an interdisciplinary, tridimensional and systemic viewpoint. U, Th, Ra and Rn behaviors have been fully investigated, making it possible to establish previsional models of Rn exhalation in scales compatible to dimensions of small habitational nuclei or even unitary dwellings.